Visualisasi 3 Dimensi Tumbuhan Langka di Pusat Konservasi Tumbuhan Kebun Raya Bogor - Rubil, Rubil; Arini, Arini; Syam, Ardiyan Saputra (ComTech: Computer, Mathematics and Engineering Applications, 2013)
Plants are an important part of the cycle of life, but often overlooked by human existence. Lots of plants are on the verge of extinction so it is difficult to see their figures. Many efforts have been done by agencies to preserve the rare plant. With the 3-dimensional visualization that replaces the figures of the ungrowing plants, the authors intend to make a 3D prototype application of rare plant encyclopedia. The goal is to simplify the users, especially visitors of Plant Conservation Center Library to see 3-dimensional model of rare plants. Theapplication is created through several stages of research, including field observations and interviews, library research, and related researches. Vaughan multimedia development is implemented for system development which has 4 stages. First is planning by searching target audiences, and making design concept of and navigation concept. Next is design and production phase using 5 activities such as storyboard, flowchart, interface design, content search and production. Alpha and Beta testing is used as the testing phase. The last isthe multiplication and distribution phase of application deployment. This application can allow users to search for information about the world of plants. For further development of the process, the application is expected torun in a web-based media to be accessible by public.